Behaviour of stainless steel beam-to-column joints — Part 1: Experimental investigation. (January 2019) - Elflah, Mohamed; Theofanous, Marios; Dirar, Samir; Yuan, Huanxin
Abstract: Research on stainless steel structures has primarily focused on the structural response of individual members, whilst the response of joints has received far less attention to date. This paper reports for the first time full-scale tests on stainless steel beam-to-column joints, subjected to static monotonic loads, whilst the companion paper reports numerical studies on similar connection typologies to the ones studied herein. The joint configurations tested include one flush and one extended end plate connection, two top and seated cleat connections, and two top, seated and web cleat connections of single-sided beam-to-column joints. All connected members and connecting parts including bolts, angle cleats and end plates are in Grade EN 1.4301 stainless steel. The full moment-rotation characteristics were recorded for each test and the experimentally derived stiffness and moment resistance for each joint was compared to the codified provisions of EN1993-1-8. It was verified that the connections displayed excellent ductility and attained loads much higher than the ones predicted by design standards for carbon steel joints. Highlights: The papers report for the first time experimental results on full-scale stainless steel beam-to-column joints. Stainless steel joints are shown to possess excellent ductility and high strength. Current design standards are assessed and found overly conservative in the strength prediction of stainless steel joints. Current design standards do not accurately predict the observed failure mode.